Correction to “Nomenclature of African species of the genus Stenodactylus (Squamata: Gekkonidae)” by Metallinou and Crochet (2013) - Crochet, Pierre-André; Metallinou, Margarita (Zootaxa, 2013)
In our recent paper on the nomenclature of the African species of the genus Stenodactylus (Metallinou & Crochet 2013) we argued that the lectotype designation made for Stenodactylus stenurus Werner, 1899 by Kratochvil et al. (2001) was invalid because the authors did not provide an express statement of the taxonomic purpose of the designation. This argument was based on Article 74.7.3 of the International Code of Zoological Nomenclature (ICZN 1999, the Code hereafter) which states: “To be valid, a lectotype designation made after 1999 must contain an express statement of the taxonomic purpose of the designation.”